The Effect of Silica Loading on the Performance and Morphology of Polyimide–Silica Hybrid Membrane - Bakar, N. S. A.; Hashemifard, S. A.; Mustafa, A. (Journal of Applied Membrane Science & Technology, 2017)
The performance of silica-polyimide hybrid membranes has been investigated for gas separation processes. The dope solution consisted of polyimide resin dissolved in NMP and silica sols at various weight percentages. The silica sols were prepared using a sol–gel process and the flat–sheet silica–polyimide hybrid membranes were cast using an immersion precipitation technique. The effects of silica sols loading on the gas transport properties of polyimide hybrid membranes and the correlation of morphology changes in the membrane structure and molecular orientation were studied. Polyimide hybrid membranes with silica sols loading ranging from 0 to 50 wt% were tested on gas permeation performance with single gas of O2, N2, CH4 and CO2. The gas permeation results showed that the hybrid membranes with 20 wt% to 25 wt% silica loading exhibited higher selectivity than the pure polyimide membrane. Morphological properties and molecular orientations of the silica–polyimide hybrid membranes were also studied using SEM and FTIR, respectively. The SEM and FTIR results confirmed that the 20 and 25 wt% of silica loading was the ideal composition of polyimide–silica hybrid membrane for gas separation.